Ethics for educational research in regions of protracted armed conflict and crisis: a participatory community project in the Lake Chad region. (6th December 2022) - Ebubedike, Margaret; Akanji, Tajudeen; Kunock, Afu Isaiah; Fox, Alison
Abstract: This paper critically considers the ethics of conducting community-based participatory research, which engages community members, including young people, as active participants in research about them, in the context of the protracted armed conflict and crisis of the Lake Chad region. We highlight the intersection of cultural practices and religious belief systems prevalent in this context, which further deepens the complexities arising from researching populations experiencing protracted armed conflict and crisis. This raises the possibilities of understanding research ethics in such contexts via the lens of a postcolonial frame. Using participatory photography allowed engagement in face-to-face collaborative data collection. In doing so, the research team was able to pay attention to verbal and non-verbal dimensions arising from community engagement, which supported learning about the community's positions and needs as a resource for thinking about how these might need accommodation in the project. It is not straightforward to lead this kind of project as researchers based in the Global North in terms of deciding what is right and what research practices would be considered just, compassionate, and trustworthy in these contexts. The approach taken was to distribute leadership in the project to include local actors such as NGOs working at local levels, community leaders (traditional and religious), as well as to draw on in-country research teams and the members of each of the participating communities. We argue that a more nuanced understanding about how to mitigate identified ethical concerns has implications for enhancing community-based research, especially when researching similar populations.